Reproductive success of female bears - Hertel, Anne G.; Bischof, Richard; Langvall, Ola; Mysterud, Atle; Kindberg, Jonas; Swenson, Jon E.; Zedrosser, Andreas (Dryad Digital Repository, 2017)
Reproductive success of female bears > 5 years of age was determined from helicopter surveys, inspection of the winter den, and activity data during denning in the years 2007 - 2016.